Prenatal transposition of great arteries diagnosis and management: a Chinese single-center study - Guo, Jie; Ling, Wen; Dang, Tingting; Guo, Shan; Ma, Hong; Huang, Qiong; Zeng, Liqin; Weng, Zongjie; Wu, Qiumei (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aimed to assess the diagnostic value of prenatal echocardiography for identifying transposition of the great arteries (TGA) during pregnancy and evaluating the associated outcomes. Methods: We conducted a retrospective analysis of 121 prenatally diagnosed patients with TGA at our hospital between January 2012 and September 2022. This analysis included prenatal ultrasound, prenatal screening, clinical management and follow-up procedures. Results: Among the 103 fetuses considered in the study, 90 (87.4%) were diagnosed with complete transposition of the great arteries (D-TGA), while 13 (12.6%) exhibited corrected transposition of the great arteries (CC-TGA). Diagnoses were distributed across the trimester, with 8 D-TGA and 2 CC-TGA patients identified in the first trimester, 68 D-TGA patients and 9 CC-TGA patients in the second trimester, and 14 D-TGA and 2 CC-TGA patients referred for diagnosis in the third trimester. Induction of labour was pursued for 76 D-TGA patients (84.4%) and 11 CC-TGA patients (84.6%), and 14 D-TGA patients (15.6%) and 2 CC-TGA patients (15.4%) continued pregnancy until delivery. Among the D-TGA patients, 9 fetuses (10.0%) underwent surgery, two of which were inadvertent fatality, while the remaining seven experienced positive outcomes. Additionally, seven TGA patients received palliative care, leading to four fatalities among D-TGA patients (5.2%), whereas 1 D-TGA patients and 2 CC-TGA patients survived. Conclusion: This study underscores the feasibility of achieving an accurate prenatal diagnosis of TGA during early pregnancy. The utility of prenatal ultrasound, the development of personalized perinatal plans, and the application of multidisciplinary treatment during delivery are conducive.